Hepatic stellate cells express synemin, a protein bridging intermediate filaments to focal adhesions. Issue 9 (16th February 2006) - Uyama, N; Zhao, L; Van Rossen, E; Hirako, Y; Reynaert, H; Adams, D H; Xue, Z; Li, Z; Robson, R; Pekny, M; Geerts, A
Abstract : Background and aims: In the liver, stellate cells play several important (patho)physiological roles. They express a broad but variable spectrum of intermediate filament (IF) proteins. The aim of this study was to investigate the expression and functions of the intermediate filament protein synemin in hepatic stellate cells (HSCs). Methods: In isolated and cultured rat HSCs, synemin expression was examined by quantitative reverse transcriptase polymerase chain reaction, western blotting, and immunocytochemistry. Protein–protein interaction between synemin and possible binding partners was investigated by co-immunoprecipitation and confocal microscopy. Results: Expression of synemin was significantly downregulated with increased culture time. In 1-day cultured HSCs, synemin associated with other IF proteins (GFAP, desmin, and vimentin), and with the focal adhesion proteins vinculin and talin, but not with α-actinin or paxillin. Synemin IF and focal adhesion proteins co-localised in long slender processes, but not in the lamellipodia. In human and rat liver tissue, the presence of synemin was investigated by immunohistochemistry. In normal rat and human livers, synemin immunoreactivity was found in HSCs, smooth muscle cells of hepatic arterioles, and nerve bundles in portal tracts, but not in portal fibroblasts. In CCl4 -intoxicated rat livers and in human cirrhotic livers, immunoreactivity for synemin in the parenchymal tissue was decreased. Thus synemin was expressed in quiescent HSCs but not in portal fibroblasts; and synemin expression decreased with HSC activation in vivo during chronic liver damage and with HSC activation in culture. Conclusions: Synemin forms heteropolymeric filaments with type-III IF proteins and acts as a bridging protein between IFs and a specific type of focal adhesions.